Spatially-explicit water balance implications of carbon capture and sequestration. (January 2016) - Sathre, Roger; Breunig, Hanna; Greenblatt, Jeffery; Larsen, Peter; Masanet, Eric; McKone, Thomas; Quinn, Nigel; Scown, Corinne
Abstract: Implementation of carbon capture and sequestration (CCS) will increase water demand due to the cooling water requirements of CO2 capture equipment. If the captured CO2 is injected into saline aquifers for sequestration, brine may be extracted to manage the aquifer pressure, and can be desalinated to provide additional freshwater supply. We conduct a geospatial analysis to determine how CCS may affect local water supply and demand across the contiguous United States. We calculate baseline indices for each county in the year 2005, and project future water supply and demand with and without CCS through 2030. We conduct sensitivity analyses to identify the system parameters that most significantly affect water balance. Water supply changes due to inter-annual variability and projected climate change are overwhelmingly the most significant sources of variation. CCS can have strong local effects on water supply and demand, but overall it has a modest effect on water balances. Highlights: We model county-level water impacts of CCS implementation in the USA through 2030. CCS increases water demand due to cooling water requirements of CO2 capture equipment. Brine from saline sequestration aquifers can be desalinated to provide additional freshwater. Inter-annual variability and climate change are most significant sources of variation. CCS and brine recovery can have significant local effects on water balance.